Caveolin-Mediated Internalization of Fmoc-FF Nanogels in Breast Cancer Cell Lines - Giovanni Smaldone; Elisabetta Rosa; Enrico Gallo; Carlo Diaferia; Giancarlo Morelli; Mariano Stornaiuolo; Antonella Accardo (MDPI AG, 2023)
Introduction: Hydrogel nanoparticles, also known as nanogels (NGs), have been recently proposed as alternative supramolecular vehicles for the delivery of biologically relevant molecules like anticancer drugs and contrast agents. The inner compartment of peptide based NGs can be opportunely modified according to the chemical features of the cargo, thus improving its loading and release. A full understanding of the intracellular mechanism involved in nanogel uptake by cancer cells and tissues would further contribute to the potential diagnostic and clinical applications of these nanocarriers, allowing the fine tuning of their selectivity, potency, and activity. The structural characterization of nanogels were assessed by Dynamic Light Scattering (DLS) and Nanoparticles Tracking Analysis (NTA) analysis. Cells viability of Fmoc-FF nanogels was evaluated by MTT assay on six breast cancer cell lines at different incubation times (24, 48, and 72 h) and peptide concentrations (in the range 6.25 × 10−4 ÷ 5·10−3 × wt%). The cell cycle and mechanisms involved in Fmoc-FF nanogels intracellular uptake were evaluated using flow cytometry and confocal analysis, respectively. Fmoc-FF nanogels, endowed with a diameter of ~130 nm and a zeta potential of ~−20.0/−25.0 mV, enter cancer cells via caveolae, mostly those responsible for albumin uptake. The specificity of the machinery used by Fmoc-FF nanogels confers a selectivity toward cancer cell lines overexpressing the protein caveolin1 and efficiently performing caveolae-mediated endocytosis.